2018
DOI: 10.3390/nu10070927
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Determinants of Polyunsaturated Fatty Acid (PUFA) Status in a High Fish-Eating Cohort during Pregnancy

Abstract: Polyunsaturated fatty acids (PUFA) are essential for neurodevelopment and the developing foetus depends on an optimal maternal status. Fish is a rich source of PUFA. The current study investigated dietary patterns, and associations with PUFA status in a high-fish consuming cohort of pregnant women in the Seychelles. At 28 weeks’ gestation, pregnant women provided a blood sample, from which serum total PUFA concentrations were measured, A Food Frequency Questionnaire (FFQ) and Fish Use Questionnaire (FUQ) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 46 publications
2
15
0
1
Order By: Relevance
“…Lederman et al [20] did not use an FFQ but asked about seafood consumption habits. Lynch et al and Davidson et al [25,26], both in the Republic of the Seychelles, reported results from FFQs conducted previously in that cohort [42,43]. Of the studies that used FFQs, 16 studies reported that the FFQ prompted responses by asking about specific species [13-15, 17, 19, 22-24, 27-29, 31, 32, 34, 36, 41].…”
Section: Question #40 What Is the Relationship Between Maternal Seafmentioning
confidence: 99%
“…Lederman et al [20] did not use an FFQ but asked about seafood consumption habits. Lynch et al and Davidson et al [25,26], both in the Republic of the Seychelles, reported results from FFQs conducted previously in that cohort [42,43]. Of the studies that used FFQs, 16 studies reported that the FFQ prompted responses by asking about specific species [13-15, 17, 19, 22-24, 27-29, 31, 32, 34, 36, 41].…”
Section: Question #40 What Is the Relationship Between Maternal Seafmentioning
confidence: 99%
“…The major n-3 polyunsaturated fatty acids, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), play key physiological roles related to health and disease, and the health benefits of n-3 fatty acids are well established [1,2,3,4,5,6,7,8,9]. Intake of fatty fish is the primary contributor of EPA and DHA in the diet, with α-linolenic acid (ALA) conversion serving as an additional, but limited, source [10].…”
Section: Introductionmentioning
confidence: 99%
“…These novel approaches have led to the discovery of new metabolites, fostered by the search for natural bioactive compounds with applications in agronomic, medical, or biofuel research. Indeed, polyunsaturated fatty acids (PUFA) are lipids with high nutritional value [15] and may have applications in the prevention of several pathologies, such as cancers or cardiovascular diseases [16,17]. Furthermore, the anti-inflammatory and antiviral properties of polar lipids have also been highlighted recently [18,19].…”
Section: Introductionmentioning
confidence: 99%